2018
DOI: 10.1111/mmi.14126
|View full text |Cite
|
Sign up to set email alerts
|

AbmR (Rv1265) is a novel transcription factor of Mycobacterium tuberculosis that regulates host cell association and expression of the non‐coding small RNA Mcr11

Abstract: SummaryGene regulatory networks used by Mycobacterium tuberculosis (Mtb) during infection include many genes of unknown function, confounding efforts to determine their roles in Mtb biology. Rv1265 encodes a conserved hypothetical protein that is expressed during infection and in response to elevated levels of cyclic AMP. Here, we report that Rv1265 is a novel auto‐inhibitory ATP‐binding transcription factor that upregulates expression of the small non‐coding RNA Mcr11, and propose that Rv1265 be named ATP‐bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 108 publications
(165 reference statements)
7
39
0
Order By: Relevance
“…Thus, we added a copy of the Mtb abmR locus upstream of the P mcr11 : GFPv fusion sequences and re‐tested the activity of P mcr11 in response to growth phase in Msm. The addition of abmR significantly increased P mcr11 activity in Msm, and rendered P mcr11 activity responsive to growth phase (Figure e), as previously observed in BCG and Mtb (Girardin et al, ). Inclusion of abmR also significantly increased the amount of stable Mcr11 detected by Northern blot in Msm (Figure d), indicating that Mcr11 is unstable even when abundantly transcribed in Msm.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Thus, we added a copy of the Mtb abmR locus upstream of the P mcr11 : GFPv fusion sequences and re‐tested the activity of P mcr11 in response to growth phase in Msm. The addition of abmR significantly increased P mcr11 activity in Msm, and rendered P mcr11 activity responsive to growth phase (Figure e), as previously observed in BCG and Mtb (Girardin et al, ). Inclusion of abmR also significantly increased the amount of stable Mcr11 detected by Northern blot in Msm (Figure d), indicating that Mcr11 is unstable even when abundantly transcribed in Msm.…”
Section: Resultssupporting
confidence: 83%
“…We also demonstrated that transcriptional termination and stable production of Mcr11 are enhanced by extended native sequence 3′ to mcr11 along with the product of the divergently transcribed adjacent gene, abmR (Figure ). The regulation of central metabolism in Mtb is consistent with mcr11 expression profiles in response to growth phase and in vivo infection (Girardin et al, ; Pelly et al, ). However, the additional requirements for TB complex specific factors for stable Mcr11 expression were unexpected, and may have broader implications for understanding sRNA expression in Mtb.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations